Zastosowanie bentomaty i ścianki ilastej jako ekranów przeciwfiltracyjnych w wałach przeciwpowodziowych = Application of bentomats and loam barrier as impermeable wall in flood banks - Asani, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article present investigation of effectiveness sealing truck elements of the flood banks with impermeable wall bentomats and protective loam partition. The testing was carried out in the area of flood banks located on the section of the Oder River in the Lubuskie Province, between 561,6 and 565,0 km of the river reaches. The filtration calculations were car-ried out in the hydrologic year 2004/2005 on the basis of hydrologic observations made in piezometer networks installed in levee fragments that differed in sealing technologies. The result of the tests is comparison of effectiveness sealing truck elements the flood banks in water filtration restriction.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); uszczelnianie wałów; filtracja wody przez wał przeciwpowodziowy; technologie uszczelnienia wałów; bentomata; ścianka ilasta; flood banks sealing; water filtration through a flood banks; sealing truck elements of the flood banks; bentomats; loam barrier